How Have the COVID-19 Pandemic Precautions Affected the Frequency of Rotavirus and Enteric Adenovirus in Pediatric Patients? - Ayşe ALICI; Samet ÇAM (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Approximately 70-80% of diarrheal cases in children are caused by viral pathogens. Viral gastroenteritis agents include rotavirus and adenovirus 40 and 41, particularly in those under two years of age, while norovirus and sapovirus can cause epidemics in individuals of all ages. In this study, we investigated the effect of Coronavirus disease-2019 (COVID-19) pandemic measures on the incidences of rotavirus and enteric adenovirus, which are the main viral agents of acute gastroenteritis in the pediatric age group. Materials and Methods: Patients <18 years of age, who were admitted to Tatvan State Hospital with the suspicion of acute gastroenteritis and whose rotavirus and enteric adenovirus antigen stool tests were analyzed, were scanned retrospectively. One year of the pre-pandemic period (01.03.2019-29.02.2020) and 1 year of the pandemic period (01.03.2020-28.02.2021) were included in the study. The rotavirus and adenovirus monthly test numbers, positivity rates, age, and gender of the patients were evaluated. Results: A total of 1,438 pediatric patient samples were analyzed during the pre-pandemic period and 345 pediatric patient samples had a preliminary diagnosis of acute gastroenteritis during the pandemic period. The adenovirus positivity rate was 1.8% (n=26) and the rotavirus positivity rate was 12% (n=173) during pre-pandemic period. These rates were 0.8% (n=3) for adenovirus and 8.6% (n=30) for rotavirus during the pandemic period, (respectively p=0.215; p=0.080). A significant decrease in stool sample analyses was observed during the pandemic (p<0.001). Rotavirus positivity rates were significantly lower in October (p=0.001), November (p=0.04), and December (p=0.04) during the pandemic period compared to the same months during the pre-pandemic period. Conclusion: As a result, COVID-19 pandemic precautions, such as maintaining social distance, wearing a mask, and complying with hygiene rules may have decreased the incidence of acute gastroenteritis and consequently reduced the number of stool samples analyzed during the pandemic period. Precautions taken during the pandemic period helped to prevent intestinal viral infections in children.